Development of a process for the concentration of the strategic tantalum and niobium oxides from tin slags. (April 2019) - Allain, E.; Kanari, N.; Diot, F.; Yvon, J.
Highlights: This process achieved a selective dissolution of the amorphous matrix of tin slag. Sequential alkaline and acid leaching cycles are used for the leaching of tin slag. The effects of various parameters on the leaching of the slag matrix are analyzed. The content of (Ta + Nb) oxides in the leaching residue is around 63%. The recovery rate of (Ta, Nb)2 O5 achieved during the process is close to 86%. Abstract: The extraction of tin through smelting of cassiterite (SnO2 ) has generated considerable amounts of slag in the main production areas of South-East Asia, Africa, and South America. Tantalum and niobium naturally occur in cassiterite deposits and are concentrated in the slag during the smelting process. Tin slags have often been disposed as industrial waste despite contents of tantalum and niobium ranging from 2 to 25%. Conventional hydrometallurgical processes for the concentration of tantalum and niobium oxides utilizing high concentration of strong acids such as HF or H2 SO4 are environmentally and economically challenging. This paper describes an original and greener approach for the selective dissolution of the slag amorphous matrix, and the concentration of tantalum and niobium oxides in a solid residue. Starting from a slag containing about 15% (Ta, Nb)2 O5, sequential alkaline and acid leaching stages resulted in the production of a 63% (Ta + Nb) oxides concentrate, which is comparable to commercial grade of mineral concentrates.